Effect of Probiotics against Marine Pathogenic Bacteria on Artemia franciscana - M. A. Badhul Haq, P. Vijayasanthi, R. Vignesh, R. Shalini, Somnath Chakraborty, R. Rajaram (Journal of Applied Pharmaceutical Science)
Presently an effort has been made to determine the effectiveness of probiotics against marine pathogenic bacterial load ingested by Artemia franciscana nauplii. In this experiment Artemia franciscana nauplii was allowed to ingest pathogenic bacterial strains, viz. Escherichiacoli, Salmonella typhi, Salmonella paratyphi, Vibrio cholerae and Shigella sp. Probiotic organism (Bioremid) was used against the pathogenic strains on Artemia franciscana nauplii. On completion of the experiment it was observed that the use of Probiotic organism (Bioremid) reduced the pathogenic bacterial load, especially that of Shigella sp. on Artemia franciscana.
Keywords: Probiotics, marine pathogenic bacteria, Artemia franciscana.